Studies on Pre-cooling and Storage of Banana for Extension of Shelf Life - Doshi, J S; Sutar, R F (Journal of Agricultural Engineering, 2010)
Pre-cooling of banana can contribute to a great extent in increasing the shelf life. Banana bunches harvested at 3/4th of full maturity and hands with blemish free uniform fingers were cut, washed, weighed, marked and given precooling (forced air cooling, hydro-cooling, dipping each at 5 degree C, 8 degree C and 10 degree C), waxed and control treatments. The temperature of cooling media and fruit pulp centre was measured. Immediately after pre-cooling, light drying and fungicidal application of Bavistin, the samples were shifted to three storage environments viz. ambient condition (30 ± 3 degree C), zero energy cool chamber (25 ± 1 degree C at 90 â€“ 95 % RH), and cold storage (13.5 ± 0.5 degree C, at 85-90 % RH). The stored samples were evaluated periodically for physiological loss in weight (PLW), spoilage, ripeness and quality (appearance, firmness, shrivelling). The wax treatment was better for banana storage at ambient temperature and in zero energy cool chamber, and at par with pre-cooling treatments for banana for cold storage. Only deciding factor was cost of waxing or pre-cooling versus shelf life extension. Pre-cooling of banana, by any of the three methods, at temperature of 5 degree C, 8 degree C or 10 degree C gave additional 5 days of shelf life in cold storage. Alternatively, shelf life advantage of 3 days could also be obtained if pre-cooled using either forced air cooling or hydro cooling at temperature of 5 degree C, 8 degree C or 10 degree C and stored under evaporative storage conditions.